APPLICATION OF CONTROLLED SOURCE AUDIO MAGNETOTELLURIC (CSAMT) AT GEOTHERMAL - S., Susilawati; Mustopa, Enjang Jaenal (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2017)
CSAMT or Controlled Source Audio-Magnetotelluric is one of the Geophysics methods to determine the resistivity of rock under earth surface. CSAMT method utilizes artificial stream and injected into the ground, the frequency of artificial sources ranging from 0.1 Hz to 10 kHz, CSAMT data source effect correction is inverted. From the inversion results showed that there is a layer having resistivity values ranged between 2.5 Ω.m – 15 Ω.m, which is interpreted that the layer is clay.